2006
DOI: 10.1177/1078345806292202
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity a Problem in a Juvenile Correctional Facility?

Abstract: This study measured changes in body mass index (BMI) of male youths upon admission and 3 months after admission to a long-term juvenile correctional facility and identified potential causes of obesity in this population. Health records for 159 youths admitted during an 18-month period were used to calculate the BMI for each. The annual dietary assessment, standard meal plans, and physical activity requirements also were reviewed. Upon admission, 12% of the youths were obese (BMI greater than 95th percentile fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…However, the increase was not statistically significant in the study by Robinson et al . , and the study by Lagarrigue et al . had a very small sample size .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…However, the increase was not statistically significant in the study by Robinson et al . , and the study by Lagarrigue et al . had a very small sample size .…”
Section: Resultsmentioning
confidence: 80%
“…In this latter study, caloric restriction was used and prisoners were involved in daily work at the prison factory and had to engage in half hour of moderate exercise by walking around prison grounds. In the studies reporting average weight gain , weight gain ranged from 0.37 lb per week in a study of male prisoners with a mean length of incarceration of 179 d to 1.1 lb per week in a study of female prisoners with a median length of incarceration of 23 d . Five studies reported the proportion of participants changing weight categories ; the proportion of participants who were OW/OB increased during incarceration in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, existing literature about prison food and nutrition offers guidance on how to comply with nutritional standards, legal requirements, and budgetary and security issues (e.g. Brisman, 2008; Cray, 2001; Edwards, Hartwell, Reeve, & Schafheitle, 2007; Foster, 2006; Herbert, Plugge, Foster, & Doll, 2012; Stein, 2000; Tammam, Gillam, Gesch, & Stein, 2012; Wakeen, 2008), and describes interventions to improve prisoner diets and help inmates lose weight (Eves & Gesch, 2003; Khavjou et al, 2007; Nikolas, 2000; Robinson, Haupt-Hoffman, Stewart, Schneider, Hamm, & Garrison, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Recent work demonstrates both incarcerated men and women are at higher risk for obesity and obesity related diseases [3][4][5][6][7][8]. This risk may be especially disproportionate for incarcerated juveniles [9] and for incarcerated women [6,[10][11][12][13]. Some of this work has documented incarceration as an independent risk factor for unhealthy weight status as well as chronic disease burden.…”
Section: Introductionmentioning
confidence: 99%